The halal product acceptance model for the religious society / Nazahah Abd. Rahim, Sutina Junos - Abd. Rahim, Nazahah; Junos, Sutina (2012)
The purpose of this paper is to examine the determinants of consumers‟ halal product acceptance within a Muslim population, a previously unexplored aspect of consumer behavior, to develop and propose a halal product acceptance model for the religious society. Since the objective function of a Muslim consumer differs from that of other consumers, it aims to establish an integrated framework to understand the influential factors involved in the product acceptance process by consumers in this society. In doing so, the Theory of Planned Behavior (TPB) which is part of the proposed framework, with the help of additional factors, religion and habit are used to shed light on how religious consumers form their intention to accept halal products such as halal food. Attitude towards accepting halal products, the influence of significant others, the perceived control over buying halal products, rulings of the religion and consumer‟s own habit predict the intention to accept halal products among Muslims. By addressing the traits that predict product acceptance, marketers can stimulate consumers to seek out new halal products and this in turn stimulates product innovation and diffusion. The paper also offers directions for future research in which the results of this paper will also be beneficial to restaurants owners for instance by offering an insight into the intentions of consumers to choose halal products.